Review Paper on Wireless Power Transmission for Charging Mobile Devices (International Journal of Engineering and Computer Science, 2017)
Wireless charging is an emerging technology. It transmits power through an air gap to various electrical devices mainly mobile devices for energy replenishment. Basically, the attempt is to make the charging process easy and user-friendly by removing physical cable connection between the mobile phone and the cable. There has been growing need in wireless field as it has enormous benefits like the user don’t have to carry mobile charger with him/her, no need to keep mobile devices near to charging socket as wires have shorter length. The mobile operators have been working to develop methodologies to reduce power consumption in the mobile devices but unfortunately, the reductions were not enough. The early adopters of wireless power are Verizon, AT&T, NTTDocomo, Softbank and KDDI. The purpose of this paper is to present brief idea on wireless power transmission as well as to present its future research scope.